Demand for improved fish feed in the presence of a subsidy: a double hurdle application in Kenya. (19th August 2016) - Amankwah, Akuffo; Quagrainie, Kwamena K.; Preckel, Paul V.
Abstract: Fish farming households' demand for improved fish feed from the private market in Kenya is potentially influenced by the government's feed subsidy program. This article applies the double‐hurdle model to a cross‐section of fish farms to analyze demand for improved fish feed from private markets, and whether the government feed subsidy program has an effect on private demand for improved feed. The results indicate that households' decisions to participate in the improved feed market are affected by the quantity of improved feed received from the government. Once the participation decision has been made, we find evidence of crowding‐in of the private improved feed sector; that is, the government's allocations of subsidized feed appear to increase private sector demand. In addition, the price of improved feed negatively affects the quantity purchased as expected. Education, extension contacts, and ease of marketing matured fish increase household propensity to purchase improved feed commercially. Policies that help reduce the price of improved feed such as reduction in tariffs on imported feeds and feed ingredients will foster demand for the feed, as will policies that facilitate marketing of fish at reasonable prices by households.